Clinical study and surgical management of acute intestinal obstruction in the adults - Gadhavi, Jaydeep M.; Charpot, Rahul (International Surgery Journal, 2020)
Background: The aim of this study was to evaluate the treatment protocol of intestinal obstruction in adults. Methods: A total of 60 patients diagnosed with intestinal obstruction were included in the study. All the patients with the provisional diagnosis of the intestinal obstruction were assessed clinically after the admission. Appropriate surgical procedures were implemented on the patients with clear signs and symptoms of acute abdominal obstruction. Surgery adopted and criteria for deciding the procedure were noted. Results: For the management of small bowl obstruction. Adhesiolysis was done in 14 patients, resection and anastomsis was done in 8 patients, in 4 patients the band release procedure was performed, hernia repair was done in 8 patients, followed by resection, hernia repair, volvulus derotation and Mekels diverticulectomy was done in 2 patients respectively. For the management of large bowl obstruction the Colostomy was done in 8 cases, resection and anastomosis in 4 cases, intussusception milking in two cases, volvulus derotation was done in 2 cases and right hemicolectomy was done in 4 cases of CA ascending colon. Conclusions: Success in the treatment of acute intestinal obstruction depends largely upon early diagnosis skilful management and treating the pathological effects of the obstruction just as much as the cause itself. Postoperative adhesions are the common cause to produce intestinal obstruction. Clinical radiological and operative findings put together can diagnose the intestinal obstruction. Mortality is still significantly high in acute intestinal obstruction.